(untitled) (Research, Society and Development, 2020)
Fruits and vegetable residues (FVR) flour were obtained from the solid residue generated from the whole processing of whole fruits (3) and vegetables (8). The purpose of this study was to analyze the FVR flour carbohydrate profile, and to propose chemical and enzymatic modification structure to use as functional ingredient. The properties such as sorption behavior, total phenolic content and antioxidant activity also were evaluated. Besides, the FVR flour was applied to produce candies. The FVR flour presented only 1-kestose (GF2) as prebiotic oligosaccharides and native condition, conformation changes from an amorphous structure after different pH conditions, that caused lower stability of the FVR flour when it was exposed to variations of aw, only supporting up to aw = 0.6. The GAB was the most suitable model to construct sorption isotherms. The phenolic content of the samples obtained through the enzymatic process was higher than that found in FVR flour, sample 10 (60.29 ± 15.12 mg) and the antioxidant activity values 0.55 ± 0.04g of sample/g DPPH. Phenolic content gum and crystal candies, respectively, is 0,289 ± 0,097 mg GAE.g-1 and 0,228 ± 0,011 mg GAE.g-1. This study shows that it is possible to promote viable and sustainable food processing without waste generation.